Printing press : ideas into type - Steffens, Bradley, 1956- (San Diego, CA : Lucent Books, 1990)
Discusses the invention of mechanical printing, from its origins in China through Gutenberg to present technology, examining typography, graphic arts, paper, bookbinding, photography, and the cultural contexts of printing.
Includes bibliographical references (p. 90-91) and index.
Keywords: Printing presses -- History -- Juvenile literature; Printing -- History -- Juvenile literature; Printing